2019
DOI: 10.31413/nativa.v7i6.7592
|View full text |Cite
|
Sign up to set email alerts
|

Fator De Resposta Produtiva De Mombaça E Marandu Ao Déficit Hídrico

Abstract: O objetivo com este estudo foi compreender o efeito da disponibilidade hídrica sobre a produtividade no capim-mombaça [Megathyrsus maximus (Jacq.) B. K. Simon & S. W. L. Jacobs] e capim-marandu [Brachiaria brizantha (Hochst. ex A. Rich.) R. D. Webster], determinando o coeficiente de resposta ao déficit hídrico (ky). O experimento foi avaliado em delineamento de blocos ao acaso, com duas forragens e três repetições. O período experimental correspondeu a doze ciclos de crescimento com intervalos fixos de col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The increase in stem height observed in the present study, due to the increase in irrigation depth, has also been observed by Lopes et al (2014), Luz et al (2008) and Alencar et al (2009), when studying grasses of the genera Brachiaria (Xaraés grass), Panicum (Tanzania grass and Mombaça grass), Pennisetum (Pioneiro grass), and Cynodon (Estrela grass), respectively. Tropical forage species are efficient in using water, which implies greater production potential (MOMBACH et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in stem height observed in the present study, due to the increase in irrigation depth, has also been observed by Lopes et al (2014), Luz et al (2008) and Alencar et al (2009), when studying grasses of the genera Brachiaria (Xaraés grass), Panicum (Tanzania grass and Mombaça grass), Pennisetum (Pioneiro grass), and Cynodon (Estrela grass), respectively. Tropical forage species are efficient in using water, which implies greater production potential (MOMBACH et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Greater availability of water favors the absorption, solubilization and transport of nutrients in plants, resulting in increments in the structural characteristics of forage species (LIMA et al, 2018;COUTINHO et al, 2020;MOMBACH et al, 2019;ARAÚJO JÚNIOR et al, 2019;BRANDÃO et al, 2017). However, the linear increase in stem height as a function of increasing irrigation depths should be carefully evaluated, as stem height restricts intake by cattle due to the physical barrier it imposes on the grazing process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Das braquiárias, observa-se na Brachiaria brizantha cv. Marandu baixa sensibilidade ao déficit hídrico (Mombach et al, 2019), o que faz deste capim uma referência para diferimento da pastagem. Contudo, este capim tem sérios problemas em solos encharcados, visto que é acometido por fungos, como Fusarium spp.…”
Section: Introductionunclassified